(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study on socio economic status and housing management practices followed by buffalo owners was undertaken in Purandar tehsil, of Pune, district Maharashtra state. For this study 150 buffalo owners were chosen randomly as respondents from 15 selected villages. Data was collected through pretested questionnaire. The owners were distributed in three groups viz., group-I, group-II and group-III on the basis of buffaloes possessed by them as up to 4, 5 to 8 and more than 9 buffaloes, respectively. Majority (50.00%) of buffalo owners were between age of 31-50 years, whereas, 14.66 % farmers were educated up to graduation level. Majority (88.33%) of buffalo owners had provided shed facility to their buffaloes. Permanent buffalo shed was provided by 73.33 % farmers. About 32.00 % farmers were providing thatched roofing, 50.66 % farmers were providing G.I. sheets and very few (17.33%) farmers were using asbestos for roofing. Majority (74.00%) farmers provided optimum size manger. There was positive and significant (P<0.01) association between number of buffaloes maintained by various groups of farmers and different housing practices viz., availability of buffalo shed, type of shed, provision of optimum size of manger, direction of byre, white wash to the byre. The association between number of buffaloes maintaide clean, comfortable stay for good health of animals and for efficient management. Inadequate and improper planning results in additional labour charges and increased costs in maintenance of shed.ned by various groups of farmer and housing practices viz., type of roof and type of wall was non-significant. Adoption of scientific housing management practices was poor in Purandar tehsil of Pune district